ANALYZING THE READING QUESTIONS OF AP12 TEXTBOOK ACCORDING TO BLOOM’S TAXONOMY - Yahya Matrouk Al Raqqad; Hanita Hanim Ismail, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study aimed to analyse the lower and higher order thinking skills of reading comprehension questions in the Action Pack 12 English Language textbook for grade twelve students in Jordan. Also, it used the content analysis in collecting, analysing, and classifying reading questions according to Bloom’s Taxonomy of the Cognitive Domain. The researcher calculated the percentage and frequencies in each unit of the textbook. The findings showed that the reading comprehension questions covered all of Bloom’s Taxonomy cognitive levels (knowledge, comprehension, application, analysis, synthesis, and evaluation). The results showed that 79 questions focused on lower thinking processes (knowledge, comprehension, and application) while 35 questions looked at the higher level of thinking processes (analysis, synthesis, and evaluation). Findings from this research recommended that the textbook authors should further develop the content of the textbook and maintain a balance between the lower-order questions and the higher-order ones where multilevel questions should be used and included at the end of each reading passages.